Analisis Pengembangan Panjang landas Pacu dan Daya Dukung Perkerasan Bandar Udara Internasional Komodo Labuan Bajo - Zahra Widya Permadi; Dewi Rintawati (Universitas Batanghari Jambi, 2026)
This study aims to analyze the runway length, thickness, and pavement bearing capacity in existing conditions to serve critical aircraft operations, especially B737-900 aircraft and its development to serve wide-body aircraft A330-300 for the next 10 years. The method used to analyze the runway pavement thickness uses FAARFIELD software and pavement bearing capacity uses COMFAA software. The quadratic trend forecasting method is used to project the number of passengers for the next 10 years based on data from 2015 to 2024. The results of the study indicate that the existing runway length of 2,750 meters is still capable of serving B737-900 aircraft operations, while the planned Airbus A330-300 aircraft requires a corrected runway length of 3,400 meters with a width of 45 meters. The results of the pavement structure evaluation using FAARFIELD show that although the existing pavement still has a structural contribution, the structural capacity is not sufficient to serve the operation of the wide-body aircraft type Airbus A330-300. Therefore, the addition of a pavement layer (overlay) is needed to increase the bearing capacity of the pavement so that it meets the operational requirements of the planned aircraft. However, the results of the analysis using COMFAA show that the PCN value of the existing pavement of 55/F/C/W/T does not meet the operational needs of the Airbus A330-300 aircraft which has an ACN value of 72.6.